Пропитка алмазного порошка расплавами Сo–Mо, Cо–Tі под действием высоких давлений и температур - Луцак, Э.Н.; Бочечка, А.А.; Романко, Л.А.; Осипов, А.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
At pressure 8 GPa the impregnation kinetics of the diamond micropowder АСМ 20/14 by liquid melt Со–Тi and Со–Мо of various concentrations have been experimentally studied. It is shown, that temperature dependences of impregnation coefficients are described by Arrhenius equation. Correlation between concentration dependences of impregnation coefficients and viscosity of corresponding binary liquid melt is determined.